Pathogen Inactivation of Cellular Blood Products—An Additional Safety Layer in Transfusion Medicine - Seltsam, Axel (Frontiers in Medicine, 2017)
In line with current microbial risk reduction efforts, pathogen inactivation (PI) technologies for blood components promise to reduce the residual risk of known and emerging infectious agents. The implementation of pathogen inactivation of labile blood components is slowly but steadily increasing. This review discusses the relevance of pathogen inactivation for the field of transfusion medicine and describes the available and emerging PI technologies that can be used to treat cellular blood products such as platelet and red blood cell units. In collaboration with the French medical device manufacturer Macopharma, the German Red Cross Blood Services developed a new UVC light-based pathogen inactivation method for platelet units, which is currently being investigated in clinical trials.